Experimenting with the Peanut Butter and Jelly Sandwich Challenge to Introduce Algorithmic Thinking and Test Case Writing - Gama, Kiev; da Costa, Andrew Diniz; Coelho, Hendi Lemos; Venieris, Ricardo Almeida; de Lucena, Carlos José Pereira (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
New approaches that offer good learning experiences driven to computer science education have been applied in different places. One of the ways adopted is the application of dynamics in classrooms that challenge students to work in groups and make relations to situations of their lives. Besides, to improve content retention and students engagement, humor is one good element that should be applied in these dynamics. The "Peanut butter and jelly sandwich challenge" is an example that allows including the idea of challenging students using humor as a support to instructional content. This paper explains how that dynamic was applied to two students' groups. The first experience was offered in a mobile programming course that follows a boot camp style and involved a multidisciplinary group with students from three universities. The dynamic applied was used to present the relevance of algorithmic thinking. The second experience used the first case as motivation, adapting it to cover contents focused on test case writing applied to students of computer science. In both cases we present results gathered, such as learning impact for the students.